Kemandirian Keuangan Daerah Kabupaten Di Provinsi Jawa Tengah - Heru Eko Prasetyo (Serat Acitya, 2020)
This study aims to determine the effect of economic growth and local original income on the level of regional financial independence in the Central Java Province in 2016 - 2018. The population in this study are all districts in Central Java Province. While the sample used is the Regency in Central Java Province totaling 29 (twenty nine) Regencies. The sampling technique in this study using the Census sample that is all populations are sampled. This study uses multiple linear regression analysis.The results of the study are the first hypothesis statement is expected that economic growth has a significant effect on the level of Regional Financial Independence, not proven. Statistical test results show a significant level of economic growth of 0.911, which means greater than a significant level of 0.05 (0.911> 0.05). This proves the results of research that economic growth has no significant effect on the level of Regional Financial Independence. The second hypothesis statement is expected that regional own-source revenue (PAD) has a significant effect on the level of Regional Financial Independence. The results of statistical tests show a significant level of regional original income of 0,000, which means it is smaller than the significant level of 0.05 (0,000 <0.05). This proves the results of the study that local revenue has a significant effect on the level of financial independence.